(3QSGdI aj eQGJH GdehLhOGJs - (3HgefjGQ Hf GdeQRHGf GdGPQHjLGf, CHh GdMSf,J (B458 (3g` s
(3ChdgG (B:s
(3GdeaGQbGJ CQHY eQGJH eNJdaI GdMbGjb GdehLhO GdPi dGSHH dg s
(3BNQgG (B:s
(3Efg dh cGf GdYbd GdgjhdGfi HGbjG eY GdYbd HGdaYd dcGfJ GdfaS HTF hGMO YGdeI hLGgdI eYkG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B77s
(3eUOQ GbJfGA GdCUd (B:s
(3djOf (B(184 BR) s
Keywords: (3GdadSaI hGdefWbs